Antiproliferative activities of chalepin and rutamarin isolated from Ruta angustifolia on selected cancer cell lines / Musa Isah Fakai - Musa Isah , Fakai (2019)
Chalepin and rutamarin isolated from the chloroform fraction of Ruta angustifolia were screened against selected cancer lines namely the human hormone-dependent breast cancer cell (MCF7), human non-hormone-dependent breast cancer cell (MDA-MB-231), human colon cancer cell (HT29), human colon carcinoma cell (HCT116) and a normal lung fibroblast cell line (MRC-5). Phytochemical investigation on the active chloroform extract led to the isolation of chalepin and rutamarin using HPLC. These compounds were then, identified by GC-MS and NMR analysis. This was followed by cytotoxicity screening using SRB assay. Based on the IC50 at the lower time point, chalepin was further investigated for its apoptotic induction on MCF7 cell through morphological analysis using both phase contrast and fluorescence microscopy; and established biochemical assays. Western blot analysis was also conducted on MCF7 treated with chalepin. For HT29 cells, rutamarin treatment followed by downstream study on protein profiling by LC-MS approach as well as western blot analysis was performed as there were no previously reported study. The active chloroform extract showed relatively higher cytotoxic activity against MCF7, MDA-MB-231, and HT29, but no activity against MRC5 (IC50 > 100g/mL). Chalepin displayed remarkable cytotoxicity against all tested cancer cell lines but no activity against MRC-5. Rutamarin on the other hand, showed remarkable cytotoxic activity only on MCF7 and HT29, whereas no activity against MDA-MB-231 and MRC5 was observed. In this study, morphological examinations identified typical apoptotic features such as membrane blebbing, chromatin condensation, DNA fragmentation, and apoptotic body formation. Phosphatidylserine externalisations, DNA fragmentation, and caspase-3 activity significantly increased whereas mitochondrial membrane potential significantly decreased in chalepin treated MCF7 cells as compared to untreated cells. Western blots results showed that the expression of pro-apoptotic proteins such as caspases, Bid and P53 were upregulated whereas cell cycle regulatory proteins such as CDK2, CDK4, cyclin A, and cyclin D were downregulated. Similarly, EGFR and its downstream cascades; (PI3K-AKT; JAK-STAT3 and Erk pathways) were also downregulated. The apoptotic effect of chalepin against MCF7 was a dose and time-dependent manner. On the other hand, Western blot results on HT29 treated with rutamarin shows that the expression of pro-apoptotic proteins such as caspases, Bid, P21, P27, and P53 was upregulated whereas cell cycle regulatory proteins such as CDK2, CDK4, cyclin A, and cyclin D were downregulated. Similarly, EGFR and its downstream cascades (PI3K-AKT; JAK-STAT3 and Erk pathways) were also downregulated. Results from proteomic profiling indicates that 2056 proteins were identified from both untreated and 6 hours rutamarin treated HT29. Following filtrations, at various levels, only 756 proteins were used for the analysis. Consequently, two sample t-test show that only one protein; mitochondrial carrier homolog 2 (MTCH2) (Q9Y6C9) was identified to be upregulated in 6 hours, whereas profile plot analysis indicated 20 proteins are having a similar pattern including the differentially expressed protein. These initial results, therefore suggest that chalepin and rutamarin may serve as potential anticancer agents that warrant further in-depth investigations.